Urgensi Penegakan Hukum bagi Anak dibawah Umur sebagai Pelaku Pembunuhan: Kajian Hukum dan Sosial - Hartanti, Fadhila Aliyah Putri (Proceedings Series on Social Sciences & Humanities, 2024)
This study examines the pressing need for legal enforcement in cases where minors are involved in murder. The research focuses on the legal and social implications of minors committing such heinous crimes, highlighting the urgency of effective legal measures to address these issues. The study draws on various sources, including legal frameworks and social studies, to provide a comprehensive understanding of the complexities surrounding minors as murderers. The study emphasizes the importance of legal enforcement in ensuring justice and protecting society from the harm caused by minors who commit murder. It also explores the social factors that contribute to such behaviors, including the role of family dynamics, peer influence, and societal pressures. The research aims to contribute to the ongoing debate about the legal and social responses to minors who commit murder, with the ultimate goal of developing more effective strategies for preventing and addressing these crimes. By examining the legal and social dimensions of this issue, the study aims to provide valuable insights for policymakers, legal professionals, and social workers seeking to mitigate the impact of minors involved in murder.